The Influence of Locus of Control and Financial Literacy on Student Financial Behavior - Gultom, Elida; Liyas, Jeli Nata (Asean International Journal of Business, 2024)
This research aims to determine the influence of locus of control and financial literacy on the financial behavior of STIE Riau students. This analysis uses independent variables, namely locus of control and financial literacy, where the dependent variable is financial behavior. The sample for this research is students from the Riau College of Economics using an accidental sampling technique. Data collection was carried out by means of a questionnaire distributed via Google Form to 100 students. The statistical method uses Multiple Linear Regression analysis with hypothesis testing, statistical tests, F test and T test. The results of this research show that partially locus of control and financial literacy have a significant effect on financial behavior. The results of the simultaneous test of locus of control and financial literacy also have a significant effect on student financial behavior. The better the locus of control (financial control) and financial knowledge, the better the student's financial behavior will be.